2007
DOI: 10.1249/mss.0b013e3180de49fe
|View full text |Cite
|
Sign up to set email alerts
|

Military Applications of Hypoxic Training for High-Altitude Operations

Abstract: Rapid deployment of unacclimatized soldiers to high mountainous environments causes debilitating effects on operational capabilities (physical work performance), and force health (altitude sickness). Most of these altitude-induced debilitations can be prevented or ameliorated by a wide range of physiological responses collectively referred to as altitude acclimatization. Acclimatization to a target altitude can be induced by slow progressive ascents or continuous sojourns at intermediate altitudes. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 41 publications
1
61
0
1
Order By: Relevance
“…Under HH conditions, the higher sleep Sa O 2 may have contributed to a lessening of AMS upon awakening but had no impact on AMS or exercise performance for the remainder of each day. ventilatory acclimatization; physical performance; hypobaric hypoxia; arterial oxygen saturation ALTITUDE ACCLIMATIZATION RESULTS from numerous interrelated physiological adjustments that compensate for hypoxemia, with augmented ventilation being one of the most important and consistently reported (17,18,22,28). Ventilatory acclimatization (VEacc) can be characterized by the progressive decrease in the end-tidal PCO 2 (PET CO 2 ) that leads to an increase in arterial O 2 saturation (Sa O 2 ) during the first several days of moderate-to high-altitude residence [hypobaric hypoxia (HH), reduced barometric pressure (P B ) and 20.9% O 2 ] (7, 28).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Under HH conditions, the higher sleep Sa O 2 may have contributed to a lessening of AMS upon awakening but had no impact on AMS or exercise performance for the remainder of each day. ventilatory acclimatization; physical performance; hypobaric hypoxia; arterial oxygen saturation ALTITUDE ACCLIMATIZATION RESULTS from numerous interrelated physiological adjustments that compensate for hypoxemia, with augmented ventilation being one of the most important and consistently reported (17,18,22,28). Ventilatory acclimatization (VEacc) can be characterized by the progressive decrease in the end-tidal PCO 2 (PET CO 2 ) that leads to an increase in arterial O 2 saturation (Sa O 2 ) during the first several days of moderate-to high-altitude residence [hypobaric hypoxia (HH), reduced barometric pressure (P B ) and 20.9% O 2 ] (7, 28).…”
mentioning
confidence: 99%
“…A comparable degree of VEacc can similarly be induced as a result of repeated daily normobaric hypoxia (NH) exposures (maintained P B and Ͻ20.9% O 2 ) using many different combinations of hypoxia duration, severity, and frequency (22). What has not been established, however, is whether NH exposure is any more effective than no treatment for mitigating undesirable outcomes such as AMS or the initial large impairment in exercise performance during subsequent HH residence (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The study in soldiers staying at 2000-3960 m a.s.l. revealed that symptoms of AMS occurred in 70% of them [26]. Another study in recruits staying in Chile at the altitude of 3550 m a.s.l.…”
Section: Incidence Of Amsmentioning
confidence: 97%
“…A proper acclimatization is of great importance for professional engagement at high altitude; however a step by step adaption process over several days seems to be more a hope than reality. In case of rescue and military [4] operations at high altitude, the exposition time and duration is often unknown and the subjects are not able to terminate the altitude stay by their own. Hypoxic chambers might be a solution to have staff prepared to leave for such missions.…”
mentioning
confidence: 99%